MRI-Guided Stereotactic System for Delivery of Intraspinal Microstimulation. Issue 13 (July 2016) - Grahn, Peter J.; Goerss, Stephan J.; Lujan, J. Luis; Mallory, Grant W.; Kall, Bruce A.; Mendez, Aldo A.; Trevathan, James K.; Felmlee, Joel P.; Bennet, Kevin E.; Lee, Kendall H.
Abstract : Study Design: Laboratory/animal-based proof of principle study. Objective: To validate the accuracy of a magnetic resonance imaging (MRI)-guided stereotactic system for intraspinal electrode targeting and demonstrate the feasibility of such a system for controlling implantation of intraspinal electrodes. Summary of Background Data: Intraspinal microstimulation (ISMS) is an emerging preclinical therapy, which has shown promise for the restoration of motor function following spinal cord injury. However, targeting inaccuracy associated with existing electrode implantation techniques remains a major barrier preventing clinical translation of ISMS. Methods: System accuracy was evaluated using a test phantom comprised of nine target locations. Targeting accuracy was determined by calculating the root mean square error between MRI-generated coordinates and actual frame coordinates required to reach the target positions. System performance was further validated in an anesthetized pig model by performing MRI-guided intraspinal electrode implantation and stimulation followed by computed tomography of electrode location. Finally, system compatibility with a commercially available microelectrode array was demonstrated by implanting the array and applying a selection of stimulation amplitudes that evoked hind limb responses. Results: The root mean square error between actual frame coordinates and software coordinates, both acquired using the test phantom, was 1.09 ± 0.20 mm. Postoperative computed tomography in the anesthetized pig confirmed spatially accurate electrode placement relative to preoperative MRI. Additionally, MRI-guided delivery of a microwire electrode followed by ISMS evoked repeatable electromyography responses in the biceps femoris muscle. Finally, delivery of a microelectrode array produced repeatable and graded hind limb evoked movements. Conclusion: We present a novel frame-based stereotactic system for targeting and delivery of intraspinal instrumentation. This system utilizes MRI guidance to account for variations in anatomy between subjects, thereby improving upon existing ISMS electrode implantation techniques. Level of Evidence: N/A